A letter by Nicolaus Steno about a cavern near Como - Aliverti, Massimo (Medicina Historica, 2022)
The present work is based on a letter that a Danish scientist of the 17th century addressed to Cosimo III, grand duke of Tuscany, to report about a recent excursion to a cavern on the mountains near Como. Niels Stensen (Niccolò Stenone) was born in Copenhagen in 1638 from a family of goldsmiths. He enrolled at the faculty of medicine in the local university, continued his medical studies in Amsterdam, and finally in Leyden where he obtained a medicine degree in 1664. Meanwhile Stensen had been appreciated for his anatomical research. Later he lived for some time in Paris where he continued his anatomical research and published his ‘Discourse on Brain’. In 1666 he settled in Florence where he was appointed as professor of anatomy at the Santa Maria Nuova hospital and became a member of the ‘Accademia del Cimento’. In Tuscany he continued his anatomical research and got involved also in other sciences. Stensen converted to Catholicism in 1667 abjuring the Lutheran faith, was ordained as a priest in 1675 and finally was appointed as a bishop in 1677. He was then transferred as apostolic vicar to Hannover and later to Hamburg. Stensen died in Schwerin in 1686. His body was transported by sea to Florence and buried in the church of San Lorenzo. Among Stensen’s geological activities there were his research excursions made in 1671 in Northern Italy to visit two Alpine caverns: the cavern of Gresta (in Trentino) and the cavern of Moncodeno (in Lombardy). The purpose of the excursions was to study the build-up and the presence of ice even during summer in those caverns. The outcome was reported in two letters addressed to the grand duke in the same year. The letter examined here, written from Milan in June 1671, reports about Stensen’s observations in the cavern of Moncodeno, situated in the Pre-Alps near Como. The scientist refutes the Aristotelian theory of ‘antiperistalsis’ that hypothesised the build-up of ice in the caverns during summer as a reaction to external heat. He states, instead, that the cold air coming from the bottom of the caverns was caused by winter ice melting because of summer heat. In this letter Stensen describes the inside of the cavern in detail, also using some drawings. That cavern, located in the Grigne and known as ‘Ghiacciaia di Moncodeno’, has also been studied recently by geologists from Milanese universities. Overall, Stensen’s letter highlights the geological and speleological interests of an author who extended his research in the field of natural sciences well beyond the old boundaries of anatomy.